2014
DOI: 10.1182/asheducation-2014.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Indolent lymphoma: follicular lymphoma and the microenvironment—insights from gene expression profiling

Abstract: As shown with gene expression profiling (GEP), the development and progression of follicular lymphoma (FL) involves complex interactions between neoplastic B cells and the surrounding microenvironment. GEP further reveals that the tumor microenvironment may predict survival in patients with FL and influence the response to therapy and the risk of transformation. Here, we briefly review GEP technology and summarize the role of the tumor microenvironment in FL diagnosis, prognosis, and transformation. Genes expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…29 In contrary, increased CD8 T cells, but not CD4 T cells, correlate with better clinical outcome in FL, whereas different subpopulations of CD4 T cells restrain or favor B cell growth. 31 Moreover, Vδ1 T cells as a subset of γ/δT cells are also expanded in DLBCL and FL. 27,30 Malignant B cells overexpress inhibitory antigens, including PD-L1, CD200, PVR and CD47 that contribute to the impairment of T cells across B cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In contrary, increased CD8 T cells, but not CD4 T cells, correlate with better clinical outcome in FL, whereas different subpopulations of CD4 T cells restrain or favor B cell growth. 31 Moreover, Vδ1 T cells as a subset of γ/δT cells are also expanded in DLBCL and FL. 27,30 Malignant B cells overexpress inhibitory antigens, including PD-L1, CD200, PVR and CD47 that contribute to the impairment of T cells across B cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In B cell lymphomas, a growing body of evidence indicates that interactions between malignant B cells and immune cells engender an immunosuppressive niche by regulating of immune cell differentiation and recruitment of regulatory T cells (Treg), pDC, suppressive tumor‐associated monocytes/macrophages and myeloid‐derived suppressor cells (MDSC) 6,7,26 . Cytotoxic lymphocytes, including CD8 T cells, γ/δT cells and NK cells play an important role in antilymphoma immunity, especially in diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL) and WM 27‐31 . Recent evidence shows an increase in effector T cell populations, while a decrease in naïve T cells has been detected in a small cohort of patients with WM and IgM MGUS 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, TAMs are biologically linked with FL, presumably providing the proper signals to not only maintain the viability of FL cells but also protect the tumor cells from the active immune system. Based on results of gene expression profiling analysis, investigators found that a defined MP-enriched gene expression pattern was associated with inferior clinical course of FL ( 54 ), indicating that the presence of TAMs in FL patients may predict clinical outcomes. In addition, researchers have used other macrophagic markers identified using immunohistochemistry, such as CD68 and CD163, to predict unfavorable outcomes of FL ( 45 47 ).…”
Section: B-cell/mp Interactions In B-cell Lymphomasmentioning
confidence: 99%
“…17,18 Similar to other B-cell lymphomas, such as follicular lymphoma, the lymph node (LN) microenvironment in CLL is thought to be the predominant site of interaction between the malignant cells and tumor-associated and tumor-specific immune cells. 19 However, data on immune abnormalities in CLL patients are primarily obtained from peripheral blood (PB) studies, and little is known about the composition of nonmalignant lymphocytes in LN tissue or how this relates to PB.…”
Section: Introductionmentioning
confidence: 99%